[2+2] Cycloadditions of Sorbyl Tosylate with Imines/1‐Azadienes: A One‐Pot Domino Approach for α‐Alkylidene‐β‐lactams and Their Computational Studies and Antimicrobial Evaluation. Issue 32 (30th August 2018) - Kumar, Yogesh; Bedi, Preet Mohinder Singh; Singh, Prabhpreet; Adeniyi, Adebayo A.; Singh‐Pillay, Ashona; Singh, Parvesh; Bhargava, Gaurav
Abstract: The manuscript describes a straightforward and atom‐efficient method for the synthesis of α ‐alkylidene‐ β ‐lactams using sorbyl tosylate and imines/1‐azadienes at high temperature (80 °C). The Density functional theory calculations have shown the prevalence of the first order kinetics in these [2+2] cycloadditions to produce mixture of 3‐butadienyl‐azetidin‐2ones and 3‐but‐2‐enylidene‐azetidin‐2‐ones in good yields. The 3‐but‐2‐enylidene‐azetidin‐2‐ones have also shown antimicrobial activity against the E . coli, S . aureus, P . aeruginosa, B . cereus and B . subtilis. Abstract : The manuscript describes a straightforward and atom‐efficient method for the synthesis of α ‐alkylidene‐ β ‐lactamsusing sorbyl tosylate with imines and 1‐azadienes at high temperature (80 °C). The Density functional theory calculations show the prevalence of the first order kinetics in these [2+2] cycloadditions to produce mixture of 3‐butadienyl‐azetidin‐2‐ones and 3‐but‐2‐enylidene‐azetidin‐2‐ones in good yields. The 3‐but‐2‐enylidene‐azetidin‐2‐ones were also evaluated for their antimicrobial activity.